"I was scared dating… who would take me with my status?"-Living with HIV in the era of UTT and U = U: A qualitative study in Johannesburg, South Africa. - Tembeka Sineke; Dorina Onoya; Idah Mokhele; Refiloe Cele; Shubhi Sharma; Patience Sigasa; Mandisa Dukashe; Laila Hansrod; Robert Inglis; Rachel King; Jacob Bor (PLOS Global Public Health, 2023)
South Africa rolled out Universal Test-and-Treat (UTT) in 2016, extending treatment eligibility to all persons living with HIV (PLHIV). We sought to understand how PLHIV in Johannesburg, South Africa, interpret and experience their HIV status, five years into the UTT era. In May 2021, we conducted in-depth interviews (IDI) (N = 27) with adult (≥18 years) PLHIV referred by HIV counsellors at three peri-urban primary healthcare clinics. We also conducted three focus group discussions (FGDs) (N = 27) with adult PLHIV recruited from clinics or from civil society organisations through snowball sampling. Follow-up interviews were conducted with 29 IDI and FGD participants. Participants were asked to reflect on their HIV diagnosis, what their HIV status meant to them and how, if at all, being HIV-positive affected their lives. Interviews and focus group discussions were audio-recorded, transcribed, translated to English, and analysed using a grounded theory approach. Participants perceived that HIV was common, that PLHIV could live a normal life with antiretroviral therapy (ART), and that ART was widely accessible. However, HIV elicited feelings of guilt and shame as a sexually transmitted disease. Participants used the language of "blame" in discussing HIV transmission, citing their own reckless behaviour or blaming their partner for infecting them. Participants feared transmitting HIV to others and felt responsible for avoiding transmission. To manage transmission anxiety, participants avoided sexual relationships, chose HIV-positive partners, and/or insisted on using condoms. Many participants feared-or had previously experienced-rejection by partners due to their HIV status and reported hiding their medication, avoiding disclosure, or avoiding relationships altogether. Most participants were not aware that undetectable HIV is untransmittable (U = U). Participants who were aware of U = U expressed less anxiety about transmitting HIV to others and greater confidence in having relationships. Despite perceiving HIV as a manageable chronic condition, PLHIV still faced transmission anxiety and fears of rejection by their partners. Disseminating information on U = U could reduce the psychosocial burdens of living with HIV, encourage open communication with partners, and remove barriers to HIV testing and treatment adherence.